The role of regulatory T cells in the pathogenesis of some bullous skin diseases - Jałocha-Kaczka, Anna; Żebrowska, Agnieszka; Waszczykowska, Elżbieta (Dermatology Review/Przegląd Dermatologiczny, 2011)
Regulatory T cells (T reg ) are a phenotypically heterogeneous group of cells, playing an important role in regulation of the immune response. To date, several subtypes of regulatory cells have been identified. The most important of them are: lymphocytes CD4+CD25+, Tr1, Th3 and NK cells. Regulatory T lymphocytes act by secretion of suppressive cytokines (IL-10, TGF-) or direct cell-to-cell interaction. Functional abnormalities of regulatory T cells are important in pathogenesis of many diseases, especially autoimmune ones. Based on published studies, the review discusses the role of regulatory T cells in pathogenesis of selected bullous skin diseases.